(untitled) - DiYanni, Robert (Boston, 2000)
This new anthology is designed for Introduction to Fiction courses. It features Robert DiYanni's clear presentation of the elements along with his three-part pedagogy of experience, interpretation, and evaluation. FICTION also includes full coverage of writing about fiction with two student papers.
Keywords: Literature,Literature,Văn học,Văn học; Collections,Bộ sưu tập